2017
DOI: 10.1002/app.44879
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun poly(2‐aminothiazole)/cellulose acetate fiber membrane for removing Hg(II) from water

Abstract: Fiber membrane adsorbent not only has the advantage of ease of handling, but also offers high specific surface area that can benefit the adsorption process when compared with powdered adsorbent. In this work, a poly(2-aminothiazole) (PAT)/cellulose acetate (CA) composite fiber membrane is prepared by a coaxial electrospinning process, and used as adsorbent for removing Hg(II) from water. The adsorption processes are investigated as functions of pH value, contact time and temperature. The results suggest that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…For the traditional single-fluid electrospinning, the filament-forming polymeric matrices must have enough molecular weight to support enough physical entanglements for forming electrospun fibers within their electrospinnable windows [50]. Few reports can be found on the directly electrospun nanofibers of oligomers because they haven't enough molecular weight and in turn no enough physical entanglements in their working fluids.…”
Section: Pure Solvent As a Sheath Fluid To Create Oligomer-loaded Funmentioning
confidence: 99%
See 1 more Smart Citation
“…For the traditional single-fluid electrospinning, the filament-forming polymeric matrices must have enough molecular weight to support enough physical entanglements for forming electrospun fibers within their electrospinnable windows [50]. Few reports can be found on the directly electrospun nanofibers of oligomers because they haven't enough molecular weight and in turn no enough physical entanglements in their working fluids.…”
Section: Pure Solvent As a Sheath Fluid To Create Oligomer-loaded Funmentioning
confidence: 99%
“…Both (a) and (b) are representative TEM images of 0.1 g PAT/1.44 g CA nanofibers with unexpected core-shell nanostructures. Reprinted with permission from[50].…”
mentioning
confidence: 99%
“…It is shown that the adsorption capacity (440.25 mg/g at 25 • C) obtained with PAT-PS particles in this work was much higher than that of many other adsorbents reported in literature. For example, the maximum adsorption capacity of a PAT/CA fiber membrane was only 177 mg/g at 25 • C [15]. The excellent adsorption properties of the PAT-PS particles for Hg(II) should be primarily ascribed to their having a high surface area available for adsorption.…”
Section: Adsorption Properties Of the Pat-ps Particlesmentioning
confidence: 99%
“…As far as we are aware, this is the first work on the synthesis of PAT in the form of conjugated polymer-coated latexes, and the adsorption properties of the PAT-coated PS composite particles, which exhibit relatively high adsorption capacity, are reported for the first time. Poly(2-aminothiazole) (PAT) is a relatively new heterocyclic conjugated polymer that can be polymerized from 2-aminothiazole (AT) by the chemical oxidative method with various oxidant/solvent systems [9][10][11][12][13][14][15][16][17]. Recently, we reported the preparation of PAT by the chemical oxidative method using copper chloride as an oxidant in aqueous solution without adding any acid [13].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to conventional electrospinning, coaxial electrospinning, which adopts a spinneret composed of two coaxial capillaries to simultaneously deliver two different solutions to form the fibers with desired structure, has attracted more and more interests in fabricating bicomponent fibers . Due to the advantage of combining the properties of the core and sheath materials, the composite fibers are promising for a variety of applications, such as multifunctional textiles, drug encapsulation and release, sensitive biochemical sensors, scaffolds for tissue engineering, and conductive materials . Special morphology and structures, such as a continuous core–shell structure, hollow structure, discontinuous core–shell structure, blend‐like morphology, and so on, can be obtained by coaxial electrospinning via controlling the preparation conditions.…”
Section: Introductionmentioning
confidence: 99%